PENERAPAN MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT (STM) DENGAN PENDEKATAN JELAJAH ALAM SEKITAR (JAS) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN 1 KAMPAR - Risa Febri Indriani Febri Indriani; Yustina '; Darmadi Ahmad Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:  A class action research has been done to improve motivation and learning result biology SMAN 1 Kampar with application of learning models Science Technology Society (SENT) with approaches Natural Roaming Around (JAS). This research was conducted from April to June 2015. The subjects were students of class X MIA1 semester totaling 34 students, consisting of 8 male students and 26 female students. The parameters in this study is motivation and student learning result. Student learning result include cognitive, attitude and skills. The results showed that motivation and learning result of students has increased. On learning motivation of 6.41% was obtained after at cycle I and increased to 10.56% at cycle II. The average score of students' cognitive learning results, namely 77.50 (B) at cycle I and increased to 84.71 (SB) at cycle II. Mastery learning students at cycle I is 82.35% and increased to 100% cycle II. On average students' attitudes is 3.58 predicate A- (SB) at cycle I and increased to 3.90 predicate A (SB) at cycle II. Skills such products LKPD and reports have increased at cycle I is 3.21 predicate B + (B) and increased to 3.58 predicate A- (SB) at cycle II. On average skill products has risen 3.43 predicate B + (B) at cycle I in the form of Mading three-dimensional (3D) and increased to 3.63 predicate A- (SB) at cycle II in the form of Bokashi. Based on the research results, it can be concluded that the application of learning models Science Technology Society (SENT) with approaches Natural Roaming Around (JAS) can improve motivation and biology learning results student of class X MIA1 SMAN 1 Kampar. Keywords: Learning SENT, JAS approach, Learning Motivation, Learning Result